1997
DOI: 10.1590/s0100-879x1997000300012
|View full text |Cite
|
Sign up to set email alerts
|

Modification of pyruvate kinase and lactate dehydrogenase in foot muscle of the sea mussel Mytilus galloprovincialis under anaerobiosis and recovery

Abstract: The modification of pyruvate kinase (PK) and lactate dehydrogenase (LDH) activity in foot muscle of the mussel Mytilus galloprovincialis during exposure to air and recovery in water was investigated. In the course of exposure to air, the activity of these enzymes measured at high and low substrate concentrations showed successive increases and decreases. Returning the mussels to water after exposure to air affected enzyme activity in a manner similar to anaerobiosis. When measuring at saturated concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The results of K M values obtained for LDH and MDH of fishes acclimated to 20 o C and submitted to hypoxia suggest that naturally intense fluctuations in dissolved environmental oxygen may result in significant changes in enzyme activity, such as the ability of enzymes to respond to acute hypoxia. Lushchak et al (1997) found differences in enzyme activity throughout anaerobiosis and recovery of a sea mussel. Shaklee et al (1977) found significant differences in enzymatic activity for liver LDH and white muscle aldolases in fishes acclimated to different oxygen concentrations.…”
Section: Resultsmentioning
confidence: 88%
“…The results of K M values obtained for LDH and MDH of fishes acclimated to 20 o C and submitted to hypoxia suggest that naturally intense fluctuations in dissolved environmental oxygen may result in significant changes in enzyme activity, such as the ability of enzymes to respond to acute hypoxia. Lushchak et al (1997) found differences in enzyme activity throughout anaerobiosis and recovery of a sea mussel. Shaklee et al (1977) found significant differences in enzymatic activity for liver LDH and white muscle aldolases in fishes acclimated to different oxygen concentrations.…”
Section: Resultsmentioning
confidence: 88%
“…A number of studies on many species have shown that fishes frequently respond to a change in environmental oxygen levels with changes within hematological parameters and alteration in physiological responses (Randall, 1993;Fernandes et al, 1995;Matsusaki et al, 1997). Enzymatic adaptations to hypoxia have already shown that there is a change in affinity of some enzymes involved in aerobic and anaerobic metabolism (Lushchak et al, 1997;Panepucci et al, 1998Panepucci et al, , 2000. Shaklee et al (1977) found significant differences in enzymatic activity for liver LDH and white muscle aldolases in fishes acclimated to different oxygen concentrations.…”
Section: Introductionmentioning
confidence: 98%